2006
DOI: 10.1097/01.mco.0000241669.24923.8d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metabolic profile in a clinical setting

Abstract: Although no unified definition for the metabolic syndrome exists, it is important to identify persons at risk, in order to reduce the resultant high morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In addition, FGR is associated with increased risk of carbohydrate intolerance or type 2 diabetes mellitus, hypertension, dyslipidemia, obesity, and cardiovascular disease in adulthood 31 . The clustering of these conditions is known as metabolic syndrome or dysmetabolic syndrome 32 …”
Section: Fetal Growth Restrictionmentioning
confidence: 99%
“…In addition, FGR is associated with increased risk of carbohydrate intolerance or type 2 diabetes mellitus, hypertension, dyslipidemia, obesity, and cardiovascular disease in adulthood 31 . The clustering of these conditions is known as metabolic syndrome or dysmetabolic syndrome 32 …”
Section: Fetal Growth Restrictionmentioning
confidence: 99%
“…Similarly to adults, no general consensus exists regarding the definition of MetS in children and adolescents [132]. Furthermore, studies published so far have used their own set of variables, number of criteria (three or four) and different cut-off points to define risk factors associated with MetS.…”
Section: Introductionmentioning
confidence: 99%
“…While there is a lack of consensus in specific clinical definitions of metabolic syndrome, prospective studies have shown it to be an important predictor of physical morbidity and mortality [ 22 - 25 ]. For example, in a comparison of four definitions based on guidelines from the World Health Organization (WHO) and the National Cholesterol Education Program (NCEP), metabolic syndrome was found to predict incidence and prevalence of diabetes mellitus in a prospective study [ 24 ].…”
Section: Introductionmentioning
confidence: 99%